2021
DOI: 10.1037/amp0000751
|View full text |Cite
|
Sign up to set email alerts
|

Virtual mental health care in the Veterans Health Administration’s immediate response to coronavirus disease-19.

Abstract: Rosen served as lead for writing -original draft and writingreview and editing. Leslie A. Morland contributed equally to writing -review and editing and served in a supporting role for writing -original draft. Lisa H. Glassman served as lead for writing -review and editing and served in a supporting role for writing -original draft. Brian P. Marx served in a supporting role for conceptualization and writing -review and editing. Kendra Weaver served in a supporting role for conceptualization, data curation, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
105
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(110 citation statements)
references
References 49 publications
3
105
0
2
Order By: Relevance
“…For example, the Veteran Health Administration in the USA have had a focus on mental health specialists video consultations long before the COVID-19 pandemic. Consequently, the expansion to more video supported treatment was relatively seamless [ 56 , 57 ]. In Australia, by quickly adapting reimbursements schemes, providers and patients rapidly adopted mental health specialists video consultations and the number of video supported psychological or psychiatric sessions increased sharply [ 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, the Veteran Health Administration in the USA have had a focus on mental health specialists video consultations long before the COVID-19 pandemic. Consequently, the expansion to more video supported treatment was relatively seamless [ 56 , 57 ]. In Australia, by quickly adapting reimbursements schemes, providers and patients rapidly adopted mental health specialists video consultations and the number of video supported psychological or psychiatric sessions increased sharply [ 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prevention/therapeutics of PTSD remains unclear. It has been suggested that group virtual discussion about the deficiencies of the day's work and what needed to be improved will be helpful to relieve the loneliness and tension of living alone and to release pressure during pandemic ( Rosen et al, 2020 ). Further investigations for understanding the risk factors of PTSD in frontline nurses of COVID-19 are needed which could provide novel avenues for prevention and therapeutics of PTSD.…”
Section: Discussionmentioning
confidence: 99%
“…Certamente, a pandemia de COVID-19 aumentou a necessidade de atendimento psicológico na população global e criou novas barreiras para o acesso presencial aos serviços. Hospitais, centros de saúde mental e outras clínicas enfrentam o desafio de fornecer cuidados remotos continuados a uma população que está sob forte estresse 1,8 .…”
Section: Discussionunclassified
“…A VHA forneceu quase 1,2 milhão de atendimentos por meio telefônico e videochamada, em abril de 2020, o que reduziu as visitas presenciais em aproximadamente 80% em comparação com o período de outubro de 2019 a fevereiro de 2020. Em junho de 2020, houve aumento de 11 vezes nos atendimentos por meio de videochamada, e incremento de cinco vezes nos contatos telefônicos em relação ao período anterior à pandemia 8 . Diante desta realidade, estudos para verificar a eficácia dos dispositivos tecnológicos ofertados devem ser incentivados 10 para que possam determinar até que ponto essas intervenções podem produzir os benefícios esperados 1 .…”
Section: Introductionunclassified